Catalytic effect of zinc oxide nanoparticles on oil-water interfacial tension - Soleimani, H. (Inst Materials Physics, 2016)
New synthesized nano materials have immensely attracted the researchers for further development of nano enhanced oil recovery method particularly in nano flooding. Interfacial tension measurement tests are the effective ways to identify proper nanomaterials for enhanced oil recovery by nano/surfactant flooding. In this work zinc oxide nano-crystallites were synthesized using self-combustion technique for application in enhanced oil recovery (EOR). The synthesized sample were used to the measure interfacial tension between their aqueous phase and crude oil phase to investigate the efficiency of the nanoparticles in reduction of interfacial tension. Therefore this research is intended to investigate the effect of Zinc Oxide (ZnO) nanoparticles towards surface/interfacial tension. Practically ZnO nanoparticles were characterized using X-ray diffraction (XRD), Field Emission Scanning Electron microscope (FESEM) in order to understand its structure, size, shape and morphology. The characterization results reveal the hexagonal structure of ZnO. Pendant drop experiment was carried out to further understand the effect of nanoparticles on Interfacial Tension (IFT). Since the Zinc Oxide solution was very âcloudyâ the drop phase could not be identified and the interfacial tension was not calculated by the software. Due to this reason, the Surface Tension (ST) was calculated with different concentration. The results show high value of ST 35.57 mN/m at 0.3 wt of ZnO nanoparticles. Â© 2016, Inst Materials Physics. All right reserved.